(untitled) (Acta Scientiarum. Biological Sciences, 2013)
To investigate the emergence of Chironomidae in different habitats of a floodplain lake of the upper Paraná river floodplain, four collection points were established: marginal regions (one with numerous macrophytes species, other dominated by only Polygonum sp.), central region and linking channel. Adults were captured by surface emergence traps assembled every three months, from May 2001 to March 2002. The traps remained for a period of about 48 hours, obtaining quantitative data for richness and abundance. 944 adults distributed into three subfamilies and 40 taxa were captured. The taxa identified at the species level were: Goeldichironomus neopictus, G. petiolicola, G. maculatus, Tanytarsus ligulatus, Parachironomus atroari, P. guarani and P. cayapo. Higher abundances were observed for Polypedilum (Tripodura) sp.1 and Tanytarsus ligulatus. There was a considerable variation in the richness among the collection points, mainly on the marginal area, with 38 taxa. In the central region (five taxa) and in the linking channel, were registered the predominance of Aedokritus sp. The higher diversity and abundance of Chironomidae in the littoral area may be related to the presence of aquatic macrophytes that provide shelter and food, resulting in increased recruitment of new individuals in this region.